Right to be punished? - Placani, Adriana (Array, 2020)
It appears at least intuitively appropriate to claim that we owe it to victims to punish those who have wronged them. It also seems plausible to state that we owe it to society to punish those who have violated its norms. However, do we also owe punishment to perpetrators themselves? In other words, do those who commit crimes have a moral right to be punished? This work examines the sustainability of the right to be punished from the standpoint of the two main theories of rights—the will and the interest conceptions. The right to be punished is shown to be largely indefensible on both accounts: on the will theory, the right to be punished conflicts with autonomy, and it can neither be claimed nor waived by a perpetrator; on the interest theory, a perpetrator’s interest in punishment, inasmuch as it exists, is not sufficient to ground a duty on the part of the state.